Correction: Real-Time Subject-Independent Pattern Classification of Overt and Covert Movements from fNIRS Signals. - Neethu Robinson; Ali Danish Zaidi; Mohit Rana; Vinod A Prasad; Cuntai Guan; Niels Birbaumer; Ranganatha Sitaram (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0159959.].